2019
DOI: 10.1186/s42269-019-0232-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest assessment of fruit quality and shelf life of two elite tomato varieties cultivated in Bangladesh

Abstract: Background: Tomatoes are now one of the most popular nutrient-dense vegetables in terms of acreage, production, yield, commercial use, and consumption that add to the Bangladesh economy and ultimately reduce poverty. With this view, a lab investigation was carried out to analyze the effects of tomato (Sofol and Roma VF) verities on different post-harvest managements to extend shelf life as well as reduce post-harvest losses.Results: This study confirmed that the fruit quality attributes (color, firmness, weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Data showed that the shelf life of tomato fruits was proportionate with the doses of CaCl 2, and it was 3.90%, 5.92%, and 9.12% higher at 1%, 1.5%, and 2% concentration of CaCl 2, respectively, relative to that in control samples. Shelf life of MT-3 tomato fruit is influenced by various pre-and post-harvest factors and calculating the number of days required to attain the full ripening stage when the fruit still maintains the acceptable marketing and eating qualities [66]. Marketing and eating quality were visually observed by the different physiological and physicochemical parameters.…”
Section: Shelf Life (Days)mentioning
confidence: 99%
“…Data showed that the shelf life of tomato fruits was proportionate with the doses of CaCl 2, and it was 3.90%, 5.92%, and 9.12% higher at 1%, 1.5%, and 2% concentration of CaCl 2, respectively, relative to that in control samples. Shelf life of MT-3 tomato fruit is influenced by various pre-and post-harvest factors and calculating the number of days required to attain the full ripening stage when the fruit still maintains the acceptable marketing and eating qualities [66]. Marketing and eating quality were visually observed by the different physiological and physicochemical parameters.…”
Section: Shelf Life (Days)mentioning
confidence: 99%
“…An unsprayed fruit was used as a positive control. The percentage of disease evidence and severity was carried out by a weight loss method using the following relationship (eq ), where DS is the percentage of disease severity, W o is the original weight of the fresh fruit, and W l is the average weight loss in moisture content after 10 d.…”
Section: Methodsmentioning
confidence: 99%
“…During storage of tomato, there is a loss of firmness due to the enhanced activity of the cell wall degrading enzymes, such as polygalacturonase and pectin methyl esterase, leading to reduction in cell‐to‐cell adhesion, resulting in loss of cell wall strength (Dijik et al., 2006; Kabir et al., 2020). The activity of enzymes generally depends on respiration rate and ethylene concentration (Sinha et al., 2019). Whereas loss of water from the tomato occurs by reduction in turgor pressure due to transpiration from the stem scars (Fitch et al., 2020).…”
Section: Influence Of Edible Coatings On Physiological Responses and ...mentioning
confidence: 99%